MONITORING GAG ISLAND DEFORESTATION USING MULTI-TEMPORAL LANDSAT 8 IMAGERY ON GOOGLE EARTH ENGINE - Aningsih, Sri; Mauluda, Alfikri Dwi (Institut Teknologi Sepuluh Nopember, 2025)
Gag Island, located in Southwest Papua Province, is a conservation area with exceptional terrestrial and marine biodiversity and rich mineral resource potential, particularly nickel. Since commercial nickel mining began in 2018, mining operations have caused significant deforestation due to land clearing for access roads, open-pit mining, and support facilities. The objective of this study is to monitor land cover changes and deforestation rates on Gag Island due to nickel mining activities, using multitemporal Landsat 8 satellite images and Normalized Difference Vegetation Index (NDVI) on Google Earth Engine (GEE) from 2017-2024. The study method includes collecting and preprocessing Landsat 8 Level 2, Collection 2, Tier 1 images in GEE, calculating NDVI, land cover classification based on NDVI values, and calculating deforested areas using QGIS. The study results demonstrate significant changes in land cover, including an increase in non-vegetation areas and a decrease in areas with dense vegetation since 2018. Despite the increase in deforestation, data for 2023-2024 indicate reclamation processes in some areas. Monitoring deforestation and forest cover changes is critical to developing mitigation measures and maintaining ecological balance in the Gag Island mining area. The study results highlight the need to implement sustainable mining practices and active environmental management.